Under the Aspect of Eternity: The Human Right to Enjoy the Arts - Barrett, Jonathan M. (The Columbia Journal of Law & the Arts, 2022)
Creation and enjoyment of art are human activities universal across time and place. It was fitting, then, for the text of the 1948 Universal Declaration of Human Rights to affirm the right to enjoyment of the arts. However, this right, as stated in article 27, is barely mentioned in subsequent United Nations covenants and declarations. This Article seeks to bring the right to enjoy the arts, in particular the visual arts, back into the limelight. For the philosopher Ludwig Wittgenstein, artworks are objects seen sub specie aeternitatis (under the aspect of eternity). This Article engages with the affirmation of the eternal urge to create and enjoy the arts as a universal human right. The Article first establishes the universality of art to explain why enjoyment of the arts has been affirmed as a universal human right. The Article then traces the development of the statement of the right in the Universal Declaration and beyond. This exercise reveals the potential tension between artists’ claims to copyright and moral rights, and other community members’ enjoyment of the visual arts. The Article considers the nature of article 27 in the contemporary world and sketches a vision of a rights-based community of art.